The impact of obesity-associated glycine deficiency on the elimination of endogenous and exogenous metabolites via the glycine conjugation pathway - Tan, Hong Chang; Hsu, Jean W.; Tai, E Shyong; Chacko, Shaji; Kovalik, Jean-Paul; Jahoor, Farook (Frontiers in Endocrinology, 2024)
Background Glycine is an integral component of the human detoxification system as it reacts with potentially toxic exogenous and endogenously produced compounds and metabolites via the glycine conjugation pathway for urinary excretion. Because individuals with obesity have reduced glycine availability, this detoxification pathway may be compromised. However, it should be restored after bariatric surgery because of increased glycine production. Objective To examine the impact of obesity-associated glycine deficiency on the glycine conjugation pathway. We hypothesize that the synthesis rates of acylglycines from endogenous and exogenous sources are significantly reduced in individuals with obesity but increase after bariatric surgery. Methods We recruited 21 participants with class III obesity and 21 with healthy weight as controls. At baseline, [1,2-13C2] glycine was infused to study the glycine conjugation pathway by quantifying the synthesis rates of several acylglycines. The same measurements were repeated in participants with obesity six months after bariatric surgery. Data are presented as mean ± standard deviation, and p-value < 0.05 is considered statistically significant. Results Baseline data of 20 participants with obesity were first compared to controls. Participants with obesity were significantly heavier than controls (mean BMI 40.5 ± 7.1 vs. 20.8 ± 2.1 kg/m2). They had significantly lower plasma glycine concentration (168 ± 30 vs. 209 ± 50 umol/L) and slower absolute synthesis rates of acetylglycine, isobutyrylglycine, tigylglycine, isovalerylglycine, and hexanoylglycine. Pre- and post-surgery data were available for 16 participants with obesity. Post-surgery BMI decreased from 40.9 ± 7.3 to 31.6 ± 6.0 kg/m2. Plasma glycine concentration increased from 164 ± 26 to 212 ± 38 umol/L) and was associated with significantly higher rates of excretion of acetylglycine, isobutyrylglycine, tigylglycine, isovalerylglycine, and hexanoylglycine. Benzoic acid (a xenobiotic dicarboxylic acid) is excreted as benzoylglycine; its synthesis rate was significantly slower in participants with obesity but increased after bariatric surgery. Conclusion Obesity-associated glycine deficiency impairs the human body’s ability to eliminate endogenous and exogenous metabolites/compounds via the glycine conjugation pathway. This impairment is ameliorated when glycine supply is restored after bariatric surgery. These findings imply that dietary glycine supplementation could treat obesity-associated metabolic complications due to intramitochondrial accumulation toxic metabolites.